How does education and mindfulness matter to high school student’s pro-environmental behaviour? - Mariani Chandra; Partono Nyanasuryanadi; Burmansah Burmansah; Tjhia Khie Khiong; Julia Surya (Jurnal Konseling dan Pendidikan, 2023)
Indonesia is one of the largest marine debris disposal countries in Asia. Due to its open dumping garbage disposal scheme and the growing population of productive age and educated demographic, there is a heightened urgency to develop an education model as a practical solution. This study aims to develop an education model that combines education and mindfulness to achieve environmental competency using a pretest-posttest control group design. The target population is 96 students in classes 11 and 12, and they are divided randomly into 2 groups called the experiment group which got the intervention and the control group which did not get any intervention. The intervention given to the experimental group was built on social learning theory and adapted to the environment and socio-culture of Jakarta, Indonesia. Pretest and posttest questionnaire were used and analyzed using t-test, paired samples t-test, and one-way ANOVA. The results shows that environmental education and mindfulness influence positively pro-environmental behaviour, and there are significant differences in posttest result of the experimental group. Our experiment demonstrates education and mindfulness can simultaneously cultivate and sustain environmental competency.